Pandemic a year later: dynamics of mental state in conditions of uncertainty - N. Yu. Galoy (Вестник университета, 2022)
The article describes the results of a longitudinal study of 1036 diary entries organised in the form of a daily description by respondents of emotional states and behavioral reactions in the first two weeks of self-isolation during the COVID-19 pandemic and exactly a year later. The analysis of the dynamics of changes in the mental state of respondents, depending on their gender and age, has been presented. Significant differences in the dynamics of mental state over the year have been revealed in the direction of improvement in the whole sample, except for 2 groups: women 18– 30 years old and 56–95 years old. Gender analysis has shown that women show a most pronounced reaction to stress, anxiety and depression at the moment and in long term perspective. Age analysis has shown that young people, students, demonstrate pronounced fluctuations in their mental state and a tendency to a negative background of experiences both at the time of the outbreak of coronavirus infection and a year later.